Soil Property and Carbon Storage Variations Affected by Land Use Type in the Semi-Arid Ethiopian Rift Valley - Asfaw, Solomon; Assen, Mohammed; U.Reddy, Ramireddy (Ethiopian Journal of Social Sciences, 2020)
This study examined the variations in soil properties, and carbon and nutrient storages under different land use types in the flood plains of Metehara, upper part of the Main Ethiopian Rift Valley.Â  The study considered four land use types: cane plantation (CP), free grazing lands (FG), traditional maize farming (MF), and restored pasture (RP). The study established four transectsÂ  with typical land use types and selected three soil sampling sites with 50m intervals from the upper-slope and the lower-slope position under each land use type. In each slope position, a 10m x 10m plot was established to collect the soil samples. A total of 24 distributed soil samples (3 land uses, and 3 replications) from 0 to 30 cm depth were collected using soil auger. The results indicate that the land use types significantly affected the soil parameters (P<0.001) whereas the slope position did not. The land use type explained the variations in soil carbon (R2 =0.77, P<0.001, df = 23), and total nitrogen (R2 =0.39, P<0.05). However, the results indicate insignificant effects on soil carbon and nitrogen variations when combining the soil properties covariate with land use factor in statistical model than the variation explained by land use type. The result also reveals that soil carbon (C) and total nitrogen (N) contents under the RP were significantly higher than the FG and MF sites. This study generally suggests how land use change has increasingly affected the semi-arid ecosystems and highlights the need to improve awareness about how human land use and land management decision impacts in the semi- arid areas of Ethiopian Rift Valley.